2015
DOI: 10.1002/elan.201500047
|View full text |Cite
|
Sign up to set email alerts
|

Partially Oxidized Graphene/Metallic Single‐Walled Carbon Nanotubes Film‐Coated Electrode for Nanomolar Detection of Dopamine

Abstract: Enriched metallic single‐walled carbon nanotubes (mSWCNTs) were dispersed in aqueous solution of partially oxidized graphene (po‐Gr). As‐prepared po‐Gr/mSWCNTs suspension was used to modify glassy carbon electrode (GCE) surface, which showed high electrocatalytic activity for dopamine (DA) oxidation in pH 7.0 phosphate buffered saline (PBS) solution. Using po‐Gr/mSWCNTs/GCE we could detect DA from 350 to 3600 nM, with a detection limit down to 25 nM in physiological condition (in pH 7.0 PBS); whereas, po‐Gr/GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…However, it has been reported that under many reaction conditions, a combination of both covalent binding or chemisorption is accompanied with an increase in D band to G band intensity ratio (I D /I G ); whereas, non-covalent doping or physisorption is accompanied with the G and 2D peaks shiing as well as a decrease in their intensity ratio (I 2D /I G ) 45 (see Table 1). 29,45 Thus our results provide clear evidence that DB is attached to the graphene basal plane.…”
Section: Gnp/db Characterizationsupporting
confidence: 62%
See 2 more Smart Citations
“…However, it has been reported that under many reaction conditions, a combination of both covalent binding or chemisorption is accompanied with an increase in D band to G band intensity ratio (I D /I G ); whereas, non-covalent doping or physisorption is accompanied with the G and 2D peaks shiing as well as a decrease in their intensity ratio (I 2D /I G ) 45 (see Table 1). 29,45 Thus our results provide clear evidence that DB is attached to the graphene basal plane.…”
Section: Gnp/db Characterizationsupporting
confidence: 62%
“…Just like BPA, trace amounts of H 2 O 2 is also encountered in food samples 19 . However, stabilization of graphene sheets in water without a surfactant has been achieved via electrostatic stabilization 27 or partial oxidation on graphene sheets during electrochemical synthesis 29,30 . This phenomena has generally been considered an insurmountable challenge, which prevents dispersion of graphene sheets 26 in water without the aid of a dispersing agent 27,28 .…”
Section: The United States Environmentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts of both the D-band and G-band are signs of structural stress on carbon bonding due to the introduced heterogeneous atom , and the type of charge carriers on the surface, respectively. It has previously been reported that both nitrogen and oxygen doping of graphitic carbon lead to an increase in the Raman shift of the D-band.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene is a two‐dimensional nanomaterial of sp 2 ‐bonded carbon with exceptional electrical 10, chemical 11, mechanical 12, and thermal properties 13. Until now, graphene has obtained numerous potential applications, including sensors 1416, transparent electrodes for optoelectronics 17, and biomedical applications 18. Among various types of preparation methods for graphene such as epitaxial growth 19, chemical vapor deposition 20, chemical oxidation exfoliation 21, solvent exfoliation has obtained considerable attention due to its convenient and gentle synthesis process 2125.…”
Section: Introductionmentioning
confidence: 99%